2021
DOI: 10.15761/jts.1000396
|View full text |Cite
|
Sign up to set email alerts
|

ACE DD polymorphism in severe COVID-19

Abstract: The insertion/deletion polymorphism of the angiotensin converting enzyme (ACE) gene, previously described in association with adult respiratory distress syndrome, may play a key role in lung injury in patients with SARS-COV2. In this paper we describe 26 patients with severe respiratory failure related to COVID-19 pneumonia that underwent genetic screening for ACE polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Annunziata et al studied the frequency of ACE I/D genotype in a series of 26 severe COVID-19 cases followed in the intensive care unit and found the ACE DD genotype was the dominant geno-type in 73% of the patients. 15 They found ACE ID and ACE II genotype frequencies of 23% and 8%, respectively. 15 In another studyof 204 patients, 67 with severe disease and 137 with mild disease, Gomez et al found that the ACE DD genotype was statistically higher in the severe disease group than in the mild disease group (46% vs 32%, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Annunziata et al studied the frequency of ACE I/D genotype in a series of 26 severe COVID-19 cases followed in the intensive care unit and found the ACE DD genotype was the dominant geno-type in 73% of the patients. 15 They found ACE ID and ACE II genotype frequencies of 23% and 8%, respectively. 15 In another studyof 204 patients, 67 with severe disease and 137 with mild disease, Gomez et al found that the ACE DD genotype was statistically higher in the severe disease group than in the mild disease group (46% vs 32%, respectively).…”
Section: Discussionmentioning
confidence: 98%
“… 15 They found ACE ID and ACE II genotype frequencies of 23% and 8%, respectively. 15 In another studyof 204 patients, 67 with severe disease and 137 with mild disease, Gomez et al found that the ACE DD genotype was statistically higher in the severe disease group than in the mild disease group (46% vs 32%, respectively). 9 However, in their risk factor analysis, they found that the ACE DD genotype was not a risk factor for severe disease.…”
Section: Discussionmentioning
confidence: 98%
“…As a matter of fact, Gomez et al ( 16 ) found that ACE1 DD genotype was more frequent in severe COVID-19 cases, suggesting that there is an association between ACE1 DD genotype and the severity of COVID-19. Furthermore, ACE1 DD genotype has been correlated with respiratory failure ( 12 ) and increased death rate ( 38 ) in patients infected with COVID-19. In addition, an ecologic meta-regression showed that there is a link between ACE1 I/D polymorphism and the recovery rate of COVID-19 whereby faster recovery was correlated with higher frequency ratio of the I/D allele ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these risk factors, genetics may play a contributing role in COVID-19 infection ( 9 ). With inconclusive data, few studies have highlighted the roles of transmembrane protease serine 2 ( TMPRSS2 ), angiotensin converting enzyme 1 ( ACE1 ), and ACE2 gene variants in the susceptibility and severity of SARS-CoV-2 infection ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In southern Italy, a small study was also conducted using 27 patient samples, focusing on severe respiratory failure associated with COVID-19 pneumonia [48]. At admission, 24 patients suffered from severe respiratory failure with paO2/FiO2 <100 mmHg and were treated with mechanical ventilation.…”
Section: Studies With Patient Samples (Clinical Studies)mentioning
confidence: 99%